Fabrication of NiSx/C with a tuned S/Ni molar ratio using Ni2+ ions and Amberlyst for hydrogen evolution reaction (HER). (21st September 2020) - Moroto, Koki; Miyake, Koji; Shu, Yasuhiro; Toyama, Yuya; Ma, Jiaojiao; Tanaka, Shunsuke; Nishiyama, Norikazu; Fukuhara, Choji; Kong, Chang Yi
Abstract: Recently, NiSx based catalysts are promising electrocatalysts for Hydrogen Evolution Reaction (HER) via water electrolysis. In particular, the S/Ni ratio is crucial to improve catalytic activity of NiSx based catalysts. Herein, we synthesized NiSx based catalysts (Ni/S/C) with a tuned S/Ni molar ratio using Ni 2+ ions exchange resin. We succeeded in synthesizing Ni/S/C with different S/Ni molar ratio in the range of 0.33–1.72 by changing Ni 2+ ions exchange degree. The combination of NiSx and conductive carbon support contributes to high catalytic activity of Ni/S/C on HER. Additionally, Ni/S/C with the S/Ni molar ratio of 0.6 showed the highest onset potential; Ni3 S2 is the most active catalyst for HER in NiSx species. Our synthesis method can easily tune the ratio of S/transition metal. This work provides a new direction for the catalyst design of transition metal sulfides and expands their utilization in sustainable catalytic reaction processes. Graphical abstract: Image 1 Highlights: NiSx doped carbons (Ni/S/C) are synthesized using Ni 2+ ion exchanged resin. S/Ni molar ratio of Ni/S/C can be tuned by ion exchange degree. Ni/S/C with S/Ni ratio of 0.60 showed the highest catalytic activity on HER. Ni3 S2 is the most active species for HER in NiSx .